Internal fixation versus total hip arthroplasty for displaced femoral neck fractures in patients aged 60 to 80 years: Patient-reported outcomes and complications - Ryo Mitsutake; Hiromasa Tanino; Go Sato; Hiroshi Ito (PLoS ONE, 2025)
Background The treatment of displaced femoral neck fractures in patients aged 60–80 years old remains controversial. Arthroplasty has been reported to have lower complication rates than internal fixation (IF). However, less is known about the outcomes as perceived by the patient. The aim of the present study (the cross-sectional study) was to evaluate the patient-reported outcome measures (PROMs) of patients aged 60–80 years old with femoral neck fractures treated with IF or total hip arthroplasty (THA). Methods We investigated 92 patients affected by displaced femoral neck fractures who were treated between January 2015 and September 2022. Forty-eight patients were treated with IF, and 44 patients with THA. The outcomes were Harris Hip Score (HHS), Hip Disability and Osteoarthritis Outcome Score (HOOS), Japanese Orthopaedic Association Hip-Disease Evaluation Questionnaire (JHEQ), visual analogue scale (VAS) for pain, and VAS for patient satisfaction at 12 months postoperatively. Complications and reoperations were continuously monitored. Results The mean patient age was 68.1 ± 6.6 years. HHS, all dimensions of the HOOS and JHEQ scores, VAS for pain, and VAS for patient satisfaction at 12 months were significantly superior in the THA group compared to the IF group. All outcome measures were superior in the THA group, with mean differences exceeding their respective minimal clinically important differences or minimal detectable changes at 12 months. The rate of major reoperations was significantly higher in the IF group (14.5%) than the THA group (2.2%). Conclusion We found that patients aged 60–80 years old who underwent THA for displaced femoral neck fractures experienced better outcomes, including PROMs, than those who underwent IF. Furthermore, THA resulted in fewer reoperations than IF.